The magnitude of depression in heart failure patients and its association with NYHA class - J. Botto; S. Martins; E. Moreira; J. Silva Cardoso; L. Fernandes (European Psychiatry, 2021)
Introduction Depression is commonly present among HF patients and is associated with adverse clinical outcomes. However, research regarding its association with New York Heart Association (NYHA) class is still scarce. Objectives To evaluate the presence of depression symptoms in HF outpatients and analyze its association with NYHA class. Methods This study is part of a larger research project (Deus Ex-Machina/NORTE-01-0145-FEDER-00026). HF patients were recruited from an outpatient clinic at a University Hospital. Exclusion criteria were: unable to communicate, severe visual acuity deficit or NYHA class IV. Sociodemographic data and NYHA class were registered. The Patient Health Questionnaire-9 (PHQ-9) was used to assess depression, with a score ≥10 indicating clinically relevant depression. Results A sample of 136 HF patients was included, with a median age of 59 (range: 24-81) years old, where 66% were men. Almost half of the patients (49%) were in NYHA class II, followed by class I (36%) and class III (15%). The median score of PHQ-9 was 4(range:0-18), with 26% showing clinically relevant depression. PHQ-9 total score was associated with NYHA class (p=0.001), with higher median scores in worse NYHA classes [class I: 3 (IQR: 5.5), class II: 4 (IQR: 8) and class III: 8.5 (IQR:9.3)]. Conclusions In this study, depression was present in 26% of HF outpatients and was associated with more severe HF symptoms. Consequently, preventing, monitoring, and treating depression in the management of these patients is recommended. Further research is needed for a deeper analysis of this association.